Histone methyltransferase KMT2D contributes to the protection of myocardial ischemic injury - Liu, Shu-Bao; Meng, Xiang-Min; Li, Yu-Meng; Wang, Jun-Meng; Guo, Hui-Hui; Wang, Chaochen; Zhu, Bing-Mei (Frontiers in Cell and Developmental Biology, 2022)
Histone H3 lysine 4 (H3K4) methyltransferase 2D (KMT2D) plays an important role in cell development in early life. However, the function of KMT2D in adult cells such as cardi-omyocytes or neurons has not been reported. In this study, cardiomyocyte-specific KMT2D knockout (KMT2D-cKO) and control (KMT2D-Ctl) mice were exposed to sham or myo-cardial ischemia (MI) surgery. Depletion of KMT2D aggravated the ischemic area, led to the increased mortality (26.5% in KMT2D-cKO vs 12.5% in KMT2D-Ctl) of the mice, and weakened the left ventricular systolic function. RNA-seq analysis in cardiac tissues iden-tified genes whose expression was changed by MI and KMT2D deletion. Combined with the genome-wide association study (GWAS) analysis, cardiac disease-associated genes Rasd1, Thsd7a, Ednra, and Tns1 were identified. The expression of the Rasd1 was significantly decreased by MI or the loss of KMT2D in vivo. Meanwhile, ChIP assays demonstrated that either MI or loss of KMT2D attenuated monomethylated H3K4 (H3K4me1) enrichment on the enhancer of Rasd1. By generating a KMT2D knockout (H9C2-KO) H9C2 monoclone, we verified that the expression of Rasd1 was controlled by KMT2D, and the expression of Rasd1 was decreased by serum starvation but not low-(O2) treatment in H9C2 cells. KMT2D has a protective effect on ischemic myocardium by regulating cardiac dis-ease-associated genes including Rasd1. KMT2D is required for the H3K4me1 deposition on the enhancer of Rasd1. Our data for the first time suggest that KMT2D-mediated Rasd1 expression may play an important protective effect on adult cells during nutritional defi-ciency caused by ischemic injury.